A little bit of oomph! - Saltzberg, Barney (New York : Workman Publishing, 2013)
Make the ordinary extraordinary by putting in just a bit of extra effort.
On lift-the-flap pages with one pull-tab.
Keywords: Creation (Literary, artistic, etc.) -- Juvenile fiction; Toy and movable books -- Specimens; Creation (Literary, artistic, etc.) -- Fiction; Toy and movable books; Lift-the-flap books